A facile approach to spiro[dihydrofuran-2,3'-oxindoles] via formal [4 + 1] annulation reaction of fused 1H-pyrrole-2,3-diones with diazooxindoles - Topanov, Pavel A.; Maslivets, Anna A.; Dmitriev, Maksim V.; Mashevskaya, Irina V.; Shklyaev, Yurii V.; Maslivets, Andrey N. (Beilstein Journal of Organic Chemistry, 2022)
There has been developed an easy synthetic approach to spiro[dihydrofuran-2,3'-oxindoles] via a highly diastereoselective formal [4 + 1] cycloaddition reaction of [e]-fused 1H-pyrrole-2,3-diones with diazooxindoles. The described novel heterocyclic systems are heteroanalogues of antimicrobial and antibiofilm fungal metabolites. The developed reaction represents the first example of involving 1H-pyrrole-2,3-diones fused at the [e]-side in a [4 + 1] annulation reaction.
Keywords: [4 + 1] annulation; catalyst-free; diazooxindole; 1H-pyrrole-2,3-diones; spirooxindole

(untitled) - Yu, B.; Zheng, Y.-C.; Shi, X.-J.; Qi, P.-P.; Liu, H.-M. (Anti-Cancer Agents Med. Chem., 2016)

(untitled) - Riedinger, C.; McDonnell, J. M. (Future Med. Chem., 2009)

(untitled) - Zak, K.; Pecak, A.; Rys, B.; Wladyka, B.; Dömling, A.; Weber, L.; Holak, T. A.; Dubin, G. (Expert Opin. Ther. Pat., 2013)

(untitled) - Arulananda Babu, S.; Padmavathi, R.; Ahmad Aslam, N.; Rajkumar, V. (Stud. Nat. Prod. Chem., 2015)

(untitled) - Zhou, L.-M.; Qu, R.-Y.; Yang, G.-F. (Expert Opin. Drug Discovery, 2020)

(untitled) - Pavlovska, T. L.; Redkin, R. G.; Lipson, V. V.; Atamanuk, D. V. (Mol. Diversity, 2016)

(untitled) - Nasri, S.; Bayat, M.; Mirzaei, F. (Top. Curr. Chem., 2021)

(untitled) - Gasperi, T.; Miceli, M.; Campagne, J.-M.; Marcia de Figueiredo, R. (Molecules, 2017)

(untitled) - Xia, M.; Ma, R.-Z. (J. Heterocycl. Chem., 2014)

(untitled) - Cheng, D.; Ishihara, Y.; Tan, B.; Barbas, C. F., III (ACS Catal., 2014)

(untitled) - Mei, G.-J.; Shi, F. (Chem. Commun., 2018)

(untitled) - Chen, J.-R.; Hu, X.-Q.; Lu, L.-Q.; Xiao, W.-J. (Chem. Rev., 2015)

(untitled) - Zhou, M.; Miao, M.-M.; Du, G.; Li, X.-N.; Shang, S.-Z.; Zhao, W.; Liu, Z.-H.; Yang, G.-Y.; Che, C.-T.; Hu, Q.-F.; Gao, X.-M. (Org. Lett., 2014)

(untitled) - Ma, X.; Peng, J.; Wu, G.; Zhu, T.; Li, G.; Gu, Q.; Li, D. (Tetrahedron, 2015)

(untitled) - Hu, X.; Xia, Q.-W.; Zhao, Y.-Y.; Zheng, Q.-H.; Liu, Q.-Y.; Chen, L.; Zhang, Q.-Q. (Chem. Pharm. Bull., 2014)

(untitled) - Xu, X.; Zhang, X.; Nong, X.; Wei, X.; Qi, S. (Tetrahedron, 2015)

(untitled) - Gomes, N. M.; Bessa, L. J.; Buttachon, S.; Costa, P. M.; Buaruang, J.; Dethoup, T.; Silva, A. M. S.; Kijjoa, A. (Mar. Drugs, 2014)

(untitled) - Zhou, J.-L.; Wang, L.-J.; Xu, H.; Sun, X.-L.; Tang, Y. (ACS Catal., 2013)

(untitled) - Liu, C.-R.; Zhu, B.-H.; Zheng, J.-C.; Sun, X.-L.; Xie, Z.; Tang, Y. (Chem. Commun., 2011)

(untitled) - Şeyma Güngör, F.; Hancıoğlu, N.; Anaç, O. (Helv. Chim. Acta, 2013)

(untitled) - Avolio, F.; Rimando, A. M.; Cimmino, A.; Andolfi, A.; Jain, S.; Tekwani, B. L.; Evidente, A. (J. Antibiot., 2014)

(untitled) - Hadi, V.; Hotard, M.; Ling, T.; Salinas, Y. G.; Palacios, G.; Connelly, M.; Rivas, F. (Eur. J. Med. Chem., 2013)

(untitled) - Mustafa, A.; Hilmy, M. K. (J. Chem. Soc., 1952)

(untitled) - Wu, Y.-C.; Cui, B.-D.; Long, Y.; Han, W.-Y.; Wan, N.-W.; Yuan, W.-C.; Chen, Y.-Z. (Adv. Synth. Catal., 2021)

(untitled) - Konovalova, V. V.; Shklyaev, Y. V.; Maslivets, A. N. (ARKIVOC, 2015)

(untitled) - Konovalova, V. V.; Maslivets, A. N. (Mini-Rev. Org. Chem., 2019)

(untitled) - Stepanova, E. E.; Babenysheva, A. V.; Maslivets, A. N. (Russ. J. Org. Chem., 2011)

(untitled) - Stepanova, E. E.; Aliev, Z. G.; Maslivets, A. N. (Russ. J. Org. Chem., 2013)

(untitled) - Stepanova, E. E.; Maslivets, A. N. (Russ. J. Org. Chem., 2014)

(untitled) - Stepanova, E. E.; Maslivets, A. N. (Russ. J. Org. Chem., 2016)

(untitled) - Stepanova, E. E.; Dmitriev, M. V.; Maslivets, A. N. (Russ. J. Org. Chem., 2017)

(untitled) - Kasatkina, S. O.; Stepanova, E. E.; Dmitriev, M. V.; Maslivets, A. N. (Russ. J. Org. Chem., 2018)

(untitled) - Kasatkina, S. O.; Stepanova, E. E.; Dmitriev, M. V.; Maslivets, A. N. (Russ. J. Org. Chem., 2018)

(untitled) - Khramtsova, E. E.; Lystsova, E. A.; Dmitriev, M. V.; Maslivets, A. N.; Jasiński, R. (ChemistrySelect, 2021)

(untitled) - Stepanova, E. E.; Dmitriev, M. V.; Maslivets, A. N. (Tetrahedron Lett., 2020)

(untitled) - Stepanova, E. E.; Dmitriev, M. V.; Maslivets, A. N. (Russ. J. Org. Chem., 2021)

(untitled) - Sabitov, A. A.; Khramtsova, E. E.; Dmitriev, M. V.; Maslivets, A. N. (Russ. J. Org. Chem., 2022)

(untitled) - Murphy, G. K.; Abbas, F. Z.; Poulton, A. V. (Adv. Synth. Catal., 2014)

(untitled) - Chuang, C.-P.; Tsai, A.-I. (Synthesis, 2006)

(untitled) - Chen, R.; Fan, X.; Xu, Z.; He, Z. (Tetrahedron Lett., 2017)

(untitled) - Liu, Y.-Q.; Li, Q.-Z.; Zhu, H.-P.; Feng, X.; Peng, C.; Huang, W.; Li, J.-L.; Han, B. (J. Org. Chem., 2018)

(untitled) - Jiang, X.-L.; Liu, S.-J.; Gu, Y.-Q.; Mei, G.-J.; Shi, F. (Adv. Synth. Catal., 2017)

(untitled) - Lu, Z.; Zhang, Q.; Ke, M.; Hu, S.; Xiao, X.; Chen, F. (J. Org. Chem., 2021)